Through-the-Wall Radar Imaging Grating-Lobe and Sidelobe Suppression Method Based on Imaginary Sign Coherence Factor - Yang, Xiaopeng; Meng, Haoyu; Qu, Xiaodong; Gao, Weicheng (IEEE signal processing letters, 2024)
In order to address the contradiction between azimuth resolution and system complexity, sparse array is employed in through-the-wall radar for the purpose of detecting moving targets in shadowed spaces. However, the radar images can be distorted due to azimuth grating-lobes and high sidelobes. To mitigate this issue, a through-the-wall radar imaging grating-lobe and sidelobe suppression method based on imaginary sign coherence factor is proposed in this letter. Theoretically, it is demonstrated that the phase across different channels is symmetrical at the azimuth grating-lobes and sidelobes in centrosymmetric radar. Then, the weight is calculated based on the positive and negative consistency of the imaginary part of the imaging results in each channel. The azimuth grating-lobes and sidelobes are suppressed by applying weight to the original image. Through simulations and experiments, the effectiveness and robustness of the proposed method are validated. The azimuth grating-lobes and sidelobes are suppressed efficiently without increasing the computation amount, demonstrating its practical feasibility.